A Longitudinal Study of Students' Perceptions of Immersive Virtual Reality Teaching Interventions - Hill, Tanya; du Preez, Hanneke (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
A series of virtual reality (VR) sessions was developed to explore students' perceptions of the use of VR as a teaching intervention during lectures in an undergraduate taxation module. The study was based on the theoretical framework of the Technology Acceptance Model (TAM) and the Educational Framework for immersive Learning (EFiL) and made use of a longitudinal multi-method research design approach. Data was gathered from 566 students over the academic year using three questionnaires which were statistically analyzed. Written reflections were also collected from students and these reflections were thematically analyzed. The results show that students were positive about participating in a VR teaching intervention before they had been exposed to VR in the classroom and that they remained positive throughout the academic year as the VR interventions were rolled out on three different occasions. Students' reflections were also overwhelmingly positive, and students believe that VR is an effective and innovative way to enhance learning. The contribution of this research can be found in its use of a longitudinal study to provide understanding of the perceptions of undergraduate taxation students of the use of VR.